2015
DOI: 10.1128/jvi.03710-14
|View full text |Cite
|
Sign up to set email alerts
|

The Human Adenovirus Type 5 E4orf4 Protein Targets Two Phosphatase Regulators of the Hippo Signaling Pathway

Abstract: When expressed alone at high levels, the human adenovirus E4orf4 protein exhibits tumor cell-specific p53-independent toxicity. A major E4orf4 target is the B55 class of PP2A regulatory subunits, and we have shown recently that binding of E4orf4 inhibits PP2A B55 phosphatase activity in a dose-dependent fashion by preventing access of substrates (M. Z. Mui et al., PLoS Pathog 9:e1003742, 2013, http://dx.doi.org/10.1371/journal.ppat.1003742). While interaction with B55 subunits is essential for toxicity, E4orf4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 102 publications
(145 reference statements)
0
13
0
Order By: Relevance
“…We found that Par3 binding was mediated by a conserved motif across Ad serotypes, proximal to a K88 residue previously shown to impact the E4orf4-Par3 interaction ( Fig. 4 A; Mui et al, 2015). Substitution of a single negatively charged residue (D90A) reduced binding, while modification of three residues (DYV to GGG, to minimize structural alteration) blocked Par3 binding without impairing interaction with PP2A ( Fig.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…We found that Par3 binding was mediated by a conserved motif across Ad serotypes, proximal to a K88 residue previously shown to impact the E4orf4-Par3 interaction ( Fig. 4 A; Mui et al, 2015). Substitution of a single negatively charged residue (D90A) reduced binding, while modification of three residues (DYV to GGG, to minimize structural alteration) blocked Par3 binding without impairing interaction with PP2A ( Fig.…”
Section: Resultsmentioning
confidence: 60%
“…3 A) for functional analyses, based on the role of Par polarity proteins in the spatial control of actin dynamics (Goldstein and Macara, 2007;Nance and Zallen, 2011). While Par3 was previously reported as an E4orf4 partner, the relevance of this interaction has not been addressed (Mui et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The Hippo pathway is often deregulated in cancer and further perturbations of the Hippo-regulated transcription program may contribute to E4orf4-induced cell death in cancer cells. It was indeed demonstrated that Yap knockdown aggravated E4orf4-induced reduction in cell viability [127].…”
Section: Nuclear Pathways Of E4orf4-induced Cell Deathmentioning
confidence: 97%
“…E4orf4 also associates with protein phosphatase 1 (PP1) phosphatases that dimerize with apoptosisstimulating protein of p53 (ASPP) proteins, and with components of the Hippo signaling pathway [127] (Section 'The PP1 phosphatase and Hippo pathway components'). However, it is not clear in which cellular compartment these interactions take place.…”
Section: Nuclear Pathways Of E4orf4-induced Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation